Lydia J. Stull papers - Stull, Lydia J.
Chiefly correspondence (1865 July-November) between and reports from Stull to officials of the United States Sanitary Commission relating to her efforts to improve conditions in military prisons just after the Civil War.
Reformer and nurse.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States Sanitary Commission -- Officials and employees; Military prisons -- United States; Reconstruction (U.S. history, 1865-1877); Nurses; Reformers